Recovery in involuntary psychiatric care: Is there a gender difference?. (2013) - Schön, Ulla-Karin
Abstract : Background : Research on recovery from mental illness and the influence of compulsory psychiatric institutional care has revealed the complexity of this concept. There is also limited knowledge regarding the impact of gender-role expectations in these contexts, and how such expectations may influence both the care and individuals' recovery processes. Aim : To explore women's and men's perceptions of the impact of compulsory inpatient care on recovery from severe mental illness. Method : Grounded theory was used to analyse 30 first-person accounts of recovery from mental illness, elicited via interviews with individuals who had been compulsorily treated in hospital and diagnosed with a severe mental illness. Results : Inpatient care at an early stage was crucial for the informants' recovery. However, there was ambivalence in their perceptions of the impact of compulsory inpatient care. The narratives confirmed gender differences as well as gender stereotypes. Conclusions : The results have implications for recovery research, in that they emphasise the importance of understanding recovery as a gender-influenced process.